Desenvolvimento e caracterização de pães tipo forma adicionados de farinha de folhas de Moringa oleífera Lam - Moraes Neto, Sansão Lopes de (2021)
In the last few years, the bakery industry has sought to meet the growing consumer demand for healthier products, especially in relation to functional foods, which have a number of health benefits. Thus, one of the strategies adopted is the partial or total substitution of wheat flour for whole flours extracted from different vegetable species. In view of the above, the present work aims to develop and characterize loaves of bread with the addition of Moringa oleifera L. leaves, as well as to evaluate the toxicity and antimicrobial effect of this raw material. Starting from a completely randomized design, the formulations of the developed breads contained 5% (PM5), 10% (PM10) and 15% (PM5) of moringa leaf flour, being subjected to physical, physical-chemical analysis, electron microscopy of scanning (SEM) and dispersive energy spectroscopy (EDS) and total phenolics. As for the raw material incorporated in the breads, in this case, the flour from the moringa leaves, its toxicity and antimicrobial effect were studied. To demonstrate the statistical significance of the different formulations, the mean values ​​of the variables were subjected to analysis of variance (ANOVA), and to verify whether changes in the formulations resulted in significant differences in the characteristics of the control formulation, the Tukey test was applied (p < 0.05). The addition of moringa significantly affected the density (0.33 - 0.67), specific volume (3.03 - 1.5), expansion index (2.05 - 1.60), number (2635 - 1152) and circularity of alveoli (0.84 - 0.71) of the developed breads. The SEM pointed out structural damages in the breads' gluten network, while the EDS highlighted calcium as the main mineral in the formulations. The pH, unlike the acidity (3.95 - 5.39) was not influenced. Colorimetric analysis revealed a product with low luminosity and a green color. The breads had a reduction in the content of carbohydrates (56.48 - 44.5) and moisture (32.38 - 30.55), and an increase in the content of proteins (7.34 - 13.11) and ash (1, 75 - 3.79). The breads showed phenolic activity (331.68 - 652.60 mg 100g -1 ), even after cooking. The aqueous extracts of moringa are non-toxic (LD 50 > 1000 µg / mL) and have an antimicrobial effect against Staphylococcus aureus, and can be used in the food industry to replace the use of synthetic preservatives and organic solvents.